Ways of Expressing Refusals in Speech Acts - Qobilova Nargisa Sulaymonbekovna; Barotova Nigina Sharofovna (International Journal on Integrated Education, 2022)
The speech act of refusal has been identified as the main challenge because it can cause undue offense and communication breakdown. In most cases, people offend their interlocutors in the process of performing the act of refusal, because the extant obstacle of linguistic proficiency is compounded by the threatening nature of the speech act .A refusal is a dispreferred response that contradicts the expectations of interlocutors; hence pragmatic competence is necessary to carry it out appropriately. Most studies have indicated that speech acts can be realized either directly or indirectly, but that they are mostly performed indirectly to “soften the blow”. The indirect performance of a speech act in its linguistic form does not clearly represent the speaker’s intention, thus requiring the addressee to decipher the intended meaning of the utterance in a particular context. The speech act of refusal has been thoroughly studied in inter-language and multicultural pragmatic linguistics. It always takes the form of a negative response to acts such as invitations, offers, requests, and suggestions. A refusal can generally be considered a commussive speech act, although exceptions are possible in situations where the participants may not be aware of the outcome.